Anti-aging effect of hydrocolloid on tartary buckwheat parfaith - BAI Ju-hong; KANG Jian-ping; ZHANG Xing-can; LIU Jian; HUA Miao-miao; YANG Jian; ZHONG Xue-ting (Liang you shipin ke-ji, 2019)
The effects of mono-hydrophilic colloid(xanthan gum,guar gum,sodium alginate,hydroxypropyl methylcellulose and carrageenan) on the anti-aging of tartary buckwheat parfait were studied with sensory evaluation and hardness as indexes,and three kinds of hydrophilic colloid with better anti-aging effect were screened out.Based on this,the optimal anti-aging agent of tartary buckwheat parfait was determined by response surface analysis method.The results showed that the optimal anti-aging agent formula was 0.13%of xanthan gum,0.17% of sodium alginate and 0.24% of carrageenan(calculated bytotal slurryweight).The storage time of tartary buckwheat parfait with compound hydrophilic colloids was prolonged by 2 times(14 days)of that without hydrocolloid the at-4 ℃.